Enhancing Learning Enthusiasm of Muthala’ah Through Team Games Tournament (TGT) at Islamic Junior High School Malang - Qurrota A'yuni; Ana Taqwa Wati (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2025)
This study aims to analyze the impact of using the Team Games Tournament (TGT) learning model in improving students' enthusiasm for learning Arabic, especially muthala’ah. This study employs a quantitative approach. Data was collected through a post-test questionnaire administered at the end of the learning process. The research design used is a true experiment design, utilizing an experimental class and a control class as a comparison, with each class comprising 30 students. The data analysis used was an independent sample t-test. The results of the independent sample t-test analysis yielded a sig value (two-tailed) of 0.000, which is less than 0.05 (0.000 < 0.05), meaning that H0 is rejected and H1 is accepted. This indicates a significant increase in students' learning motivation. Thus, there is a difference in students' learning motivation when using the Team Games Tournament (TGT) learning model. Students' activities during the learning process also showed active participation, resulting in positive differences before and after the intervention. This indicates that the TGT learning model can create an active and effective learning environment and support students' learning motivation.